PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. HUTAMA KARYA (PERSERO) JAKARTA - Irawan Noor (Jurnal Ekonomi dan Industri, 2019)
Hutama Karya (Persero) runs its business in the construction field, of course it has goals and targets to be achieved. Achievement of company goals can not be separated from what is given or the contribution of the work of each individual employee in it. Discussing a person's performance according to Payaman (2005) there are three factors that affect the performance of employees or employees, namely individual factors, organizational support, and management support. Research by Riri, and Anita (2016) and I Wayan Sutya Kumara and I Wayan Utama (2016) revealed that training affected employee performance. Then Watie (2016) and Fernanda M.B, Christoffel, and Frederik G. (2017) revealed that motivational training is also important for shaping employee performance.